Peran Kesadaran Orang Tua dalam Mendorong Perkembangan Kreativitas Anak Usia Dini di KB Al Hilmiyah Pasanggar - Zuaibah; Nurul Hidayati; Desi Ismawati (ABATATSA: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study aims to determine the role of parental awareness in encouraging the development of creativity in early childhood. By using qualitative research methods, data obtained through the results of observations and interviews. Early childhood education is a development aimed at children from birth to the age of six years. A high level of awareness, most parents can understand that creativity is an important ability that must be developed from an early age, they are aware that creativity helps children solve their own problems, can also help children to think critically and help children to adapt to their surroundings.